Kilisli Rifat Bilge'nin Hayatı ve Fikirleri - Bilgiç, Hasan Fevzi (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2020)
Tez, Rifat Bey’in araştırılması hedefiyle yazılmıştır. Kilisli Muallim Rifat Bilge pek çok kaynak eserin neşrini yapmasına rağmen lisansüstü seviyesinde herhangi bir incelemenin konusu olmamıştır. Türkiyat çalışmalarına ömrünü adamış, Arapça ve Farsça eserleri neşrederek kültürümüze kazandırmış olan Kilisli Rifat Bilge’nin hayatı, eğitimi ve meslekteki yılları, tezin ilk bölümünde araştırılmıştır. Rifat Bey’in makalelerinden bazıları Anılar ve İnsanlar (1997,Ankara) ismiyle basılmıştı. Tezin ikinci kısmında bu makaleler değerlendirilip Rifat Bey’in fikir hayatı ve görüşleri tartışıldı. Son bölümde, Rifat Bey’in tashihini yaptığı, çevirisini yaptığı ve telif ettiği eserler üzerinde duruldu. İstinsah ettiği eserlerin ise künye bilgileri verildi. Rifat Bey, İstanbul yıllarında hocalık yaparken aynı zamanda eski eserlerle de ilgiliydi. Gerek çeviri şeklinde gerekse metin tashih ve kritiği yoluyla pek çok eseri neşretti. Bu anlamda Türk tarihi ve Türk edebiyatı için büyük katkıları oldu. Kilisli Rifat Bey’in Anılar ve İnsanlar isimli eserindeki bazı bilgileri kullanırken ihtiyatlı olmak gerekiyordu. Bir taraftan makalelerdeki ve hatıralarındaki bazı yanlışlara odaklanırken diğer taraftan olayların kişileri ve asılları araştırıldı. Rifat Bey’i tanımlamak gerekirse ona kitabiyat uzmanı, filolog, musahhih, tercüman, müstensih, naşir ve okuyan (kâri, tarayıcı) denebilir. Rifat Bey muallim sıfatıyla da pek çok öğrenci yetiştirdi.

The thesis was written with the aim of researching Rifat Bey.Although Kilisli Rifat has published many sources, it has not been the subject of any research at postgraduate level. In this thesis, the life, education and years of the profession of Rifat Bilge, who devoted his life to Turcology studies, were investigated. The first part of the thesis focused on these issues. Some of Rifat Bey's articles were published under the name Memories and People (1997, Ankara). In the second part of the thesis, these articles were examined. Rifat Bey's idea life and views were discussed. In the last section, the works that Rifat Bey corrected, the works he translated, and his works were introduced. Imprint information was given for the works that were copied. While Rifat Bey was teaching in Istanbul, he was also interested in ancient works. He published many works, both in translation and through text correction and criticism. In this sense, he made great contributions to Turkish history and Turkish literature. While using some information on Rifat Bey's Memories and People, it was necessary to be cautious. On the one hand, while focusing on some mistakes in articles and memories, on the other hand, the people and originals of the events were investigated. To describe Rifat Bey, he can be called a librarian, philologist, literature specialist, translator, proofreader, editor and reader (scanner). Rifat Bey trained many students as teacher
Kilisli Rıfat Bilge's Life and His Ideas
Keywords: Kilisli Muallim Rifat; Türk Kültürü; Çeviri; Naşir; Tashih; Kilisli Muallim Rifat; Turkish Culture; Translation; Editor; Revise